Penggunaan Buku Cerita Dwi Bahasa Untuk Meningkatkan Kemampuan Pelafalan Kosakata Bahasa Inggris - Ismi Adinda; Chandra Setiawan; Nurul Lita Kurniawati; Vinny Solagracia Mesah; Jessika Natalia; Elisa Lestari; Alifia Intan Febriani; Rifda Nuranbia; Faizul Wahid; Serliana Buku (Universitas Pamulang, 2023)
This community service activity aims to improve students' English pronunciation skills through reading bilingual story books at pondok pesantren Al-Hanif, Serua, Ciputat, South Tangerang. The activity refers to the process of providing bilingual storybook reading training by female students at pondok pesantren Al Hanif that are guided by Pamulang University students. PMKM is carried out using the SQ3R method which stands for survey, question, read, recall/recite, and review. In its implementation, students provide training to female students and an introduction to material about what and how to read bilingual storybooks to be able to improve their pronunciation skills and understand the contents of stories for students at pondok pesantren Al-Hanif. In carrying out PMKM activities, students of Pamulang University divided into three activities for female students at pondok pesantren Al-Hanif, namely group division and teaching how to read bilingual storybooks, female student evaluation sessions by appointing one person from each group to read in front of all groups, and word games sessions. It makes students enthusiastic and trains their vocabulary.Keywords: Bilingual story books, SQ3R, English pronunciation